Knowledge of Primary School Teachers Regarding First Aid In Baghdad Al-Rusafa - Al-Robaiaay, Yossra Kalaf Hanoon (AL-Kindy College Medical Journal, 2013)
Background: A basic knowledge and understanding of first aid can be invaluable for individuals to be able to provide emergency care in the event of an accident, possibly saving lives and minimizing injury. Since injury is the fifth leading cause of death and children at the age of primary school are liable for accidents and lack of knowledge and good judgment of their teachers may lead to dangerous consequences when emergencies occur. Training teachers how to deal with accidents is of obvious importance. Objectives: To estimate the adequacy of primary school teachers’ knowledge of first aid concerning external bleeding and fractures and Whether there’s a difference in knowledge in regard to years spent in teaching or the teaching subject and to decide whether primary school teachers need training or not. Methods: This study is a cross-sectional Study was done over 5 months (from 01/Dec/2010 to 01/May/ 2011) in five randomly chosen primary schools in different regions in Baghdad/ Al-Rusafa,carried out on 100 primary school teachers without inclusion or exclusion criteria. Statistical analysis: Chi-Square was calculated by MiniTab Program to estimate significance. The significance level was set at P<0.05. Results: Of the 100 participants, 4% had good knowledge, 19% had fair knowledge and 77% had poor knowledge, 26% were science teachers, 9% were social studies teachers, 43% were literature teachers and 22% were sport/art teachers. No significant difference was found for their knowledge (p value=0.41).Also participants were classified according to the years they spent in teaching. No significance was found for their knowledge (p value=0.82). Conclusions: Primary school teachers’ knowledge of first aid concerning external bleeding and fractures is poor and certainly inadequate.No difference was found in regard to how many years spent in teaching and difference in teaching subjects also has no effect on their knowledge.